Implementing Research-Based Pedagogical Approaches in Uzbek Higher Education: Strategies for Institutionalization and Sustainable Adoption (Passagens: Revista Internacional de História Política e Cultura Jurídica, 2025)
This analysis uses a qualitative multiple case study approach to construct a strategy for the sustainable institutionalization of research-based pedagogical practices (RBPA) within the higher education system of Uzbekistan. The data were collected using semi-structured in-depth interviews among 40 participants (faculties, education administrators, and local policymakers) and analysis of policy and institutional documents from four sample universities. Findings are testaments to a broad theoretical consciousness among RBPA’s faculty members (80.3%) relative to its inconsistent practice (42.1%) because of six significant structural obstacles: motivational system misfit (4.7 out of 5), inadequate time resources (4.4), constrained professional capability, rigid curriculum, fragmented support services, and uneven leadership commitment. Analysis also uncovered a broad stakeholder priority gap: while professors prioritize workload reduction and tangible rewards most, administrators value national ranking alignment the most. The proposed solutions were presented in a three-tier framework: Macro, promoting reengineering policies of resource distribution according to teaching and research output; Meso, incorporating RBPA in quality control mechanisms and establishing education development centers; and Micro, organizing professional learning communities and training based on context. The study highlights that sustainability of transformation relies on two fundamental conditions: firstly, eco-localization of models commensurate with the disciplinary characteristics, technological foundation, and cultural milieu of Uzbekistan; and, secondly, anchoring educational innovation in the “organizational DNA” of universities through redesigning of such fundamental processes as curriculum planning and learning assessment. Application of these measures cumulatively, establishing virtuous circles among the three tiers, will lead to improving quality of education, improving learning achievements, and increasing the world competitiveness of the country’s higher education.